Factors influencing pregnancy intentions and contraceptive use: an exploration of the 'unmet need for family planning' in Tanzania. Issue 1 (2nd January 2017) - Rusibamayila, Asinath; Phillips, James; Kalollela, Admirabilis; Jackson, Elizabeth; Baynes, Colin
Abstract: Estimation of unmet need for contraception is pursued as a means of defining the climate of demand for services and the rationale for family planning programmes. The stagnation of levels of unmet need, as assessed by Demographic and Health Surveys, particularly in sub-Saharan Africa, has called into question the practical utility of this measure and its relevance to policies and programmes in settings where evidence-based guidance is needed the most. This paper presents evidence from qualitative research conducted in rural Tanzania that assesses the diverse context in which pregnancy intentions and contraceptive behaviours are formed. The multi-level sets of influences on intentions and behaviours – that is, the dichotomous components used to calculate unmet need for family planning – are reviewed and discussed. While results lend support to the concept that unmet need exists and that services should address it, they also attest to the synergistic influences of individual, spousal, organisational and societal factors that influence the implementation of childbearing preferences. Altogether, the analysis suggests that ways for assessing and addressing unmet need in Tanzania, and similar settings, be revised to reflect contextual influences that not only shape individual preferences, but constrain how individuals implement them.